Tamoxifen inhibits transforming growth factor-α gene expression in human breast carcinoma samples treated with triiodothyronine - Conde, S. J. [UNESP]; Luvizotto, R. A M [UNESP]; Sibio, M. T. [UNESP]; Katayama, M. L H; Brentani, M. M.; Nogueira, Célia Regina [UNESP] (Springer Nature, 2008)
Objectives: To examine the effects of triiodothyronine (T3), 17β-estradiol (E2), and tamoxifen (TAM) on transforming growth factor (TGF)-α gene expression in primary breast cancer cell cultures and interactions between the different treatments. Methods and results: Patients included in the study (no.=12) had been newly diagnosed with breast cancer. Fresh human breast carcinoma tissue was cut into 0.3-mm slices. These slices were placed in six 35-mm dishes on 2-ml organ culture medium. Dishes received the following treatments: dish 1: ethanol; dish 2: T3; dish 3: T3+TAM; dish 4: TAM; dish 5: E2; dish 6: E2+TAM. TGF-α mRNA content was normalized to glyceraldehyde-3-phosphate dehydrogenase mRNA levels. All tissues included in this study were positive for estrogen receptor (ER) and thyroid hormone receptor expression. Treatment with T3 for 48 h significantly increased TGF-α mRNA levels compared to controls (15-fold), and concomitant treatment with TAM reduced expression to 3.4-fold compared to controls. When only TAM was added to the culture medium, TGF-α mRNA expression increased 5.3-fold, significantly higher than with all other treatment modalities. Conclusion: We demonstrate that TGF-α mRNA expression is more efficiently upregulated by T3 than E2. Concomitant treatment with TAM had a mitigating effect on the T3 effect, while E2 induced TGF-α upregulation. Our findings show some similarities between primary culture and breast cancer cell lines, but also some important differences: a) induction of TGF-α, a mitogenic protein, by TAM; b) a differential effect of TAM that may depend on relative expression of ER α and β; and c) supraphysiological doses of T3 may induce mitogenic signals in breast cancer tissue under conditions of low circulating E2. ©2008, Editrice Kurtis.
Keywords: Breast cancer samples; Estrogen; Tamoxifen; TGF-α; Triiodothyronine; cyclin D1; estradiol; estrogen receptor alpha; estrogen receptor beta; glyceraldehyde 3 phosphate dehydrogenase; liothyronine; messenger RNA; tamoxifen; thyroid hormone receptor; transforming growth factor alpha; adult; aged; breast carcinoma; cancer cell culture; clinical article; controlled study; culture medium; drug mechanism; female; gene expression regulation; human; human cell; human tissue; mitogenicity; upregulation; Adult; Aged; Aged, 80 and over; Breast Neoplasms; Carcinoma; Cell Culture Techniques; Down-Regulation; Drug Interactions; Estradiol; Female; Gene Expression Regulation, Neoplastic; Humans; Middle Aged; Transforming Growth Factor alpha; Tumor Cells, Cultured